Determination of 12 herbal compounds for estimating the presence of Angelica Gigas Root, Cornus Fruit, Licorice Root, Pueraria Root, and Schisandra Fruit in foods by LC-MS/MS. Issue 9 (1st September 2020) - Ahn, Su-Jin; Kim, Hyung Joo; Lee, Ayoung; Min, Seung-Sik; In, Sangwhan; Kim, Eunmi
ABSTRACT: A wide variety of plant raw materials thought to promote health are used as herbal medicines as well as foods. However, there is no legal maximum or minimum concentration limit on any herbal compound when these plant raw materials are used in processed foods. Legally, these processed foods are regulated only for harmful substances, and there is no other guarantee of their contents. Therefore, the objective of this study was to determine the concentrations of 12 herbal compounds (nodakenin, decursin, decursinol angelate, morroniside, loganin, glycyrrhizic acid, liquiritigenin, puerarin, daidzin, schisandrin, gomisin A, gomisin N) in commonly used plant raw materials, such as "Angelica Gigas root", "Cornus Fruit", "Liquorice Root", "Pueraria Root", and "Schisandra Fruit"; and also in 45 processed foods, using high-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS). Method validation was performed successfully using the parameters of specificity, linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy, precision, matrix effect, extraction recovery, and stability. The 12 herbal compounds were determined to be present in all the foods advertised as containing each ingredient, although in very low concentrations in some cases. Three solid samples labelled as 100% pure material from one herbal species also contained herbal compounds found in others, so that intentional or unintentional adulteration was suspected.